Délimiter la pseudo-clivée en contexte oral : le rôle de so, marqueur discursif - Florine Berthe; Isabelle Gaudy-Campbell (Discours)
This article focuses on the structure of discourse in spoken English through the study of the pseudo-cleft construction and the discourse marker so, when it occurs in the right co-text of this syntactic configuration. In spoken English, pseudo-clefts introduce complex units with limits that can be difficult to perceive. The discourse marker so will be analysed for its capacity to delineate this syntactic structure. The study of this limit will be informed by semantico-pragmatic, prosodic and syntactic considerations.Based on a corpus of spoken English comprising over two hundred occurrences, three configurations will be distinguished. So will first be studied for its capacity to confirm that a pseudo-cleft has reached its ending point. It will also be considered for its capacity to delay the ending point of the pseudo-cleft construction. In this case, the unit introduced by so, while signalling a prosodic and semantico-pragmatic continuity, contributes to the syntactic complexity of the pseudo-cleft. Eventually, so will be addressed for its capacity to blur the limit of the pseudo-cleft by adding semantic complexity to a discourse unit where the limit had seemingly already been reached.